THE IMPORTANCE OF INDEPENDENT WORK OF STUDENTS GUIDED BY THE PROFESSOR AT UNIVERSITY - Popova, Elena (Studiul Artelor şi Culturologie: istorie, teorie, practică (Online), 2020)
The evolution of the educational system started in the last decade of the 20th century. It requires shifting the emphasis of the educational process towards student-centered learning. The organization of independent activity of students is the processand the result of an interaction between a teacher and students in creating conditions for successful advancement of students to a higher level of this activity while constantly reducing external and strengthening internal control over the process and the result of this activity. Now the role of independent work has grown so much that it has to be specially planned.